2010
DOI: 10.1007/s10165-010-0309-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of total knee arthroplasty on disease activity in patients with established rheumatoid arthritis: 3-year follow-up results of combined medical therapy and surgical intervention

Abstract: Though excellent clinical results have been reported for total knee arthroplasty (TKA) in rheumatoid arthritis (RA) patients, the medium-term effect of TKA on RA disease activity remains unknown. This analysis aimed to assess changes in disease activity after TKA in patients with established RA. We analyzed the systemic effects of TKA on RA disease activity 3 years after intervention. Routine clinical and laboratory assessments were recorded at baseline, less than less than 0.5 years after TKA, and 3 years aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…TKA was performed on this knee joint, and after this procedure, symptoms and laboratory data dramatically improved when the patient was again treated with infliximab and MTX. Of interest, Yano et al [25] analyzed the systemic effects of TKA on RA disease activity 3 years after surgical intervention. While no significant changes in medications were noted, the average dose of prednisolone and the DAS28 tended to decrease over time.…”
Section: New Surgical Approaches In the Era Of Biological Dmardsmentioning
confidence: 99%
See 1 more Smart Citation
“…TKA was performed on this knee joint, and after this procedure, symptoms and laboratory data dramatically improved when the patient was again treated with infliximab and MTX. Of interest, Yano et al [25] analyzed the systemic effects of TKA on RA disease activity 3 years after surgical intervention. While no significant changes in medications were noted, the average dose of prednisolone and the DAS28 tended to decrease over time.…”
Section: New Surgical Approaches In the Era Of Biological Dmardsmentioning
confidence: 99%
“…While no significant changes in medications were noted, the average dose of prednisolone and the DAS28 tended to decrease over time. It was concluded that TKA, which is known to result in good clinical outcomes for damaged knees, has a secondary systemic effect on RA disease activity for at least 3 years [25].…”
Section: New Surgical Approaches In the Era Of Biological Dmardsmentioning
confidence: 99%
“…Несмотря на то, что эндопротезирование крупных суставов при ревматоидном артрите у взрослых пациен-тов является широко применяемым методом оперативно-го лечения [6,7], до сих пор операции на крупных суставах при наличии активного ревматоидного артрита пред-ставляют сложную задачу как для ортопедов-хирургов, так и для ревматологов, осуществляющих дальнейшее ведение этих больных. Тотальное эндопротезирование тазобедренного сустава у подростков является редко используемым методом лечения [8].…”
unclassified
“…Несмотря на то что эндопротезирование крупных су-ставов при РА явилось величайшей вехой в ревмоортопе-дии [8][9][10][11][12][13][14][15], до сих пор операции на крупных суставах при наличии активного РА представляют сложную задачу как для ортопедов-хирургов, так и для ревматологов, осущест-вляющих дальнейшее ведение этих больных.…”
unclassified
“…Отдаленные резуль-таты оценивались ортопедами-травматологами в основном по общепринятым параметрам в хирургии [11-13, 16, 17], и лишь в отдельных наблюдениях обсуждались показатели КЖ [12,14]. До сих пор остается спорным вопрос об изменении активности РА после эндопротезирования суставов [15].…”
unclassified